Oil-Type Sunflower Cost-Return Budget in North Central and Northeast Kansas - O'Brien, Daniel M.; Duncan, Stewart R.; Olson, Brian L.S (My University, 2008)
This publication provides estimated cost and returns for forward farm planning for producing sunflowers in north central and northeastern Kansas.
MF2144_2008_10
Keywords: MF2144; Crops; Economics; MF